(untitled) (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2023)
This study explains how certain women in Chitral, Pakistan attains the status of spirit mediumship (Pari Khan) – a process where certain women attain the status and qualification to host spirits through which they claim to heal illnesses. For data collection, the study conducted in-depth interviews with spirit media, their assistants and clients, shamans, and clinicians; collected cases studies of possessed persons and their lived experiences of illness and healing; and conducted participant observations with spirit media (Pari Khan) to observe the healing rituals in its natural setting. The study reveals that patriarchal culture and oppressive norms frustrate women to the extent of illnesses that are locally interpreted as ‘spirit possession.’ As per the local practice, the treatment of the illness lies in either exorcism or domestication of the spirit. In the case of domestication, the possessed women (patients) gradually learn to live with the spirit and become its host. Such a woman is locally called Pari Khan, who gains considerable attention and social status by virtue of her alleged spiritual powers to heal various illnesses. The authors argue that spirit possession and mediumship, though provide relative empowerment to women, take away attention from women’s social and psychological deprivation.